Proton pump inhibitor use and risk for recurrent Clostridioides difficile infection: a systematic review and meta-analysis. (May 2021) - D'Silva, Kristin M.; Mehta, Raaj; Mitchell, Michael; Lee, Todd C.; Singhal, Vibha; Wilson, Marnie Goodwin; McDonald, Emily G.
Abstract: Objectives: Proton pump inhibitor (PPI) therapy is a potentially modifiable risk factor for recurrent Clostridioides difficile infection (CDI). Citing an absence of clinical trials, many guidelines do not provide recommendations for addressing PPI management. Our aim was to perform an updated systematic review and meta-analysis evaluating the association between PPI use and recurrent CDI addressing prior methodological limitations. Methods: Data sources were MEDLINE and EMBASE. Eligible studies were cohort and case–control studies; there were no restrictions on study setting or duration of follow-up. Participants were adults with prior CDI who did or did not receive PPI therapy and were assessed for recurrent CDI. Summary (unadjusted) odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using a random effects model. Prespecified subgroup analyses were performed to explore heterogeneity including study design, study quality, duration of follow-up, adjustment for confounders, and outcome definition. Results: Sixteen studies were included in the meta-analysis, comprising 57 477 patients with CDI, of whom 6870 (12%) received PPIs. The rate of recurrent CDI was 24% in patients treated with PPIs versus 18% in those who were not. A meta-analysis that pooled unadjusted odds ratios demonstrated higher odds of recurrent CDI in patients who received PPIs (OR 1.69, 95%CI 1.46–1.96) versus those who did not. There was moderate heterogeneity between studies (I 2 56%); however, a sensitivity analysis restricted to studies with 56 days of follow-up substantially reduced the heterogeneity (OR 1.59, 95%CI 1.36–1.85; I 2 12%). An analysis restricted to multivariate studies that combined adjusted ORs also demonstrated higher odds of recurrent CDI in patients who received PPIs (OR 1.49, 95%CI 1.12–2.00). No publication bias was identified. Conclusions: We found significantly higher odds of recurrent CDI among users of PPIs that persisted across multiple sensitivity analyses. These results support stronger recommendations for PPI stewardship at CDI diagnosis.